The Flow of Garbage: From Laurence to Phong - Pagan, Nicholas Osborne (SARE: Southeast Asian Review of English, 2017)
The Oxford English Dictionary gives as its first definition of ’garbage,’ ’the offal of an animal used for food, especially the entrails. Rarely the entrails of a man.’ After being used to refer to ’discarded parts of butchered fowls’ or ’food wastes as from a kitchen,’ garbage later came to designate ’any matter that is no longer wanted or needed,’ or ’anything that is completely worthless . . . or vile.’ The word ’garbage’ is preferred in this essay to ’trash’ because ’garbage,’ though sometimes used as an adjective (’the garbage chute’), is almost always employed as a noun and never a verb. You can lose your temper and ’trash’ someone else’s or even your own apartment, but you cannot ’garbage’ an apartment. Thus the word ’garbage,’ invariably a noun, is good at retaining its connection to ’thingness’ as in the above definitions - whether it be the thingness of food waste, superfluous matter or items deemed useless or extremely unpleasant.